Radar studies of plasma parameters in the polar cap and the auroral zone - Bjoland, Lindis Merete (Journal of Atmospheric and Solar-Terrestrial Physics, 2018)
Incoherent scatter radar measurements are an important source for studies of ionospheric plasma parameters. Data from the EISCAT Svalbard radar (ESR), which covers the polar cap and cusp, and from the EISCAT Tromsø radars, which covers the auroral zone, can be used to obtain information about the electron density, electron- and ion temperature, and line-of-sight plasma velocity. As the ESR started operations in 1996, and the Tromsø UHF radar in 1981, the accumulated database covers several solar cycles, giving a unique overview of the polar ionosphere. In this dissertation, the accumulated EISCAT database is used to study variations in the polar ionosphere on several time scales. The dependence of ionospheric parameters on season, time of day, solar cycle and geomagnetic activity has been investigated. A comparison between the ESR data and the International Reference Ionosphere (IRI) model was conducted, in order to understand how well the IRI model reproduces the polar cap ionosphere during different ionospheric conditions. The comparison showed that the IRI model is biased towards an underestimation of the F-region polar cap electron density. Furthermore, we derived the Hall conductivity from the Tromsø UHF data and used this to search for trends in the peak height of the Hall conductivity and in the E-region ion temperature. Such trends are expected to occur due to the anthropogenic emissions of greenhouse gases. However, as these trends are expected to be very small, no conclusive trend could be found with the present instrumentation. Lastly, we studied high latitude depletion regions, and observed an early morning depletion region in the polar cap ionosphere. This region expands with increasing geomagnetic activity. ESR ion temperature measurements show a heating at approximately the same time as the depletion region, suggesting that this depletion region might be connected to ion frictional heating.